PENDAMPINGAN MODEL MANAJEMEN ORGANISASI BAGI UNIT-UNIT PELAKSANA DI KELURAHAN MERJOSARI KOTA MALANG - Mahendaringratry, Ayudya; Handaratri, Anitarakhmi (UNIVERSITAS PGRI MADIUN, 2020)
Abstract. In an organization, it is necessary to do proper management based on the initial agreement with all its members and the organization's management that has been determined. Actually organization management is an art to make its members want to work together on the same platform. Of course, effective management is needed to ensure the profitability of the organization. Merjosari Kelurahan Malang is a non-profit government organization that has several implementing units in it. So far these units have not yet carried out good organizational management, limited to the needs of their members without thinking about whether they can be developed according to the demands of the times. Organizational management training is needed to increase the knowledge of managers and members of the organization so that it can organize the organization optimally. This training consists of management training, administration and simple financial system. Before starting the training, questionnaires were given in advance to find out the extent of the participants' knowledge about organizational management, obtained incorrect answers which amounted to 62.56% which means that many participants did not understand how to properly manage the organization. After the training was carried out, the results of the second questionnaire obtained correct answers amounting to 78.60% which could be interpreted that the participants had understood the basics of organizational management and were able to apply them in the implementing units. It is expected that from the results of this training participants can optimally manage and develop their organizations Abstrak. Dalam sebuah organisasi, maka perlu dilakukan pengelolaan yang benar berdasarkan kesepakatan awal bersama seluruh anggotanya serta manajemen organisasi yang telah ditetapkan. Sebenarnya manajemen organisasi merupakan suatu seni untuk membuat anggotanya mau bekerja bersama-sama dengan platform yang sama. Tentunya dibutuhkan manajemen yang efektif untuk menjamin profitabilitas organisasinya. Kelurahan Merjosari Malang merupakan organisasi pemerintah non profit yang memiliki beerapa unit pelaksana di dalamnya. Selama ini unit-unit terseut belum melaksanakan manajemen organisasi yang baik, sebatas pada kebutuhan anggotanya tanpa memikirkan aakah nantinya dapat dikembangkan sesuai tuntutatn jaman. Dibutuhkan pelatihan manajemen organisasi untuk menambah pengetahuan pengelola dan anggota organisasi sehingga dapat menata organisasi secara optimal. Pelatihan ini terdiri dari pelatihan manajemen, administrasi dan sistem keuangan sederhana. Sebelum memulai pelatihan, diberikan terlebih dahulu kuesioner untuk mengetahui sampai sejauh mana pengetahuan peserta tentang manajemen organisasi, diperoleh jawaban salah yaitu sebesar 62,56 % yang berarti banyak peserta belum mengerti bagaimana mengelola organisasi yang benar. Setelah dilaksanakan pelatihan, maka hasil kuesioner kedua diperoleh jawaban benar yaitu sebesar 78,60 % yang dapat diartikan bahwa peserta telah memahami dasar-dasar manajemen organisasi dan mampu mengaplikasikannya di unit-unit pelaksana. Diharapkan dari hasil pelatihan ini peserta dapat secara optimal mengelola dan mengembangkan organisasinya.